THU0130 PATTERNS OF COGNITIVE DECLINE IN RHEUMATOID ARTHRITIS: RESULTS OF CASE CONTROL STUDY NESTED IN A POPULATION-BASED COHORT. (2nd June 2020) - Toyoda, T.; Chipping, J.; Dainty, J.; Jeffs, S.; Hornberger, M.; Mioshi, E.; Verstappen, S.; Yates, M.; Macgregor, A.
Abstract : Background: The risk of cognitive decline and dementia is of particular interest for patients exposed to prolonged inflammation. In rheumatoid arthritis (RA), the inflammatory mechanisms that are central to the disease's pathology share many features with those seen in Alzheimer's disease (AD). However, published reports on the strength and direction of the putative associations with cognitive decline and dementia in RA are conflicting and the potential impact of immunomodulation has not been fully established. This study reports on a case control analysis comparing the results of a cognitive test conducted in RA cases from a longitudinal population register with healthy controls. The relationship between test outcomes, disease characteristics, and treatment is examined. Objectives: To characterise differences in cognitive function as assessed by a validated test battery between a group of patients with RA and a matched sample of healthy controls. To investigate disease and treatment related factors that might have an impact on the cognitive function of patients with RA. Methods: A total of 38 people with RA were selected at random from subjects who had enrolled on the Norfolk Arthritis Register as part of the ICORA (Investigation of Cognition in RA) Study. The register is a large longitudinal inception cohort of patients recruited from both primary and secondary care. The study subjects were over 55 years old with a diagnosis of RA defined by the ACR criteria. Cognitive function was assessed using the Addenbrooke's Cognitive Examination III (ACE-III) battery. The ACE-III is a validated screening test for dementia that evaluates five cognitive domains (attention, memory, verbal fluency, language and visuospatial skills). A cut off value of 82 is indicative of cognitive impairment. The ACE-III scores in the cases were compared with scores from 29 healthy population-based controls matched for age and sex. Results: The mean age of the patient and control groups was 69 years. The RA patients had a mean disease duration of 9.8 years and had been taking DMARDs for 7.1 years. Among the patient group with RA, 14 (37%) scored below 82 compared with none in the group of healthy controls. The mean ACE-III scores of both groups are shown in the table below: After adjusting for age, sex, BMI and smoking status, significant differences were seen in the ACE-III total (adjusted mean difference(SE)=8.67(1.77); p<0.001), memory (adjusted mean difference(SE)=4.16(1.03); p<0.001), fluency (adjusted mean difference(SE)=2.29(0.67); p=0.001) and visuospatial (adjusted mean difference(SE)=1.36(0.38); p<0.001). There was no difference in attention (p=0.19) or language (p=0.10). Among the patients with RA there was no clear association between disease duration and ACE-III Total scores; however, there was a trend for increasing cognitive scores in those who had been taking DMARDs for longer (<5 years: mean ACE-III Total=84.1; 5-10 years: 85.0: 11-14 years: 85.4; >14 years: 89.6). Conclusion: This study provides evidence to suggest that patients with established RA are at increased risk of cognitive decline when compared with healthy controls. The pattern of cognitive deficit, predominantly involving visuospatial and memory function, is consistent with an Alzheimer's disease profile. Our data suggest a potential role for DMARDs in reducing the rate of cognitive decline in patients with RA. Disclosure of Interests: Tasuku Toyoda: None declared, Jacqueline Chipping: None declared, Jack Dainty: None declared, Stephen Jeffs: None declared, Michael Hornberger: None declared, Eneida Mioshi: None declared, Suzanne Verstappen Grant/research support from: BMS, Consultant of: Celltrion, Speakers bureau: Pfizer, Max Yates: None declared, Alex MacGregor: None declared